1987
DOI: 10.2737/fpl-gtr-54
|View full text |Cite
|
Sign up to set email alerts
|

Bolted-connection design

Abstract: Recent failures of bolted connections have raised doubts about our knowledge of their design. Some of the design criteria are based on research conducted more than 50 years ago. This paper compares results found in the literature, using the European Yield Theory as a basis of comparison, to summarize what is known about bolted-connection design and what needs further research. By putting all this information in one place we hope to help engineers and architects design safer timber buildings and structures. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Traditionally, dowel‐type wood connections have been modelled based on Johansen’s model [2], proposed in 1945, which has been incorporated in design codes [3, 4]. Johansen proposed a beam (dowel) on foundation (wood) model based on maintaining equilibrium normal to the dowel and balancing internal and external moments.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, dowel‐type wood connections have been modelled based on Johansen’s model [2], proposed in 1945, which has been incorporated in design codes [3, 4]. Johansen proposed a beam (dowel) on foundation (wood) model based on maintaining equilibrium normal to the dowel and balancing internal and external moments.…”
Section: Introductionmentioning
confidence: 99%
“…McLain and Thangjitham (1983) examined this theory for bolted wood connections loaded parallel-to-grain and found good agreement between predicted and observed values. Soltis and others (Soltis et al 1986iSoitis andWilkinson 1987) found agreement between predicted and observed values for paralleland perpendicular-ta-grain loading.…”
Section: Drift Boltsmentioning
confidence: 55%
“…Similar equations are developed for other connection geometries. The development of the equations is well documented by Soltis et al (1986Soltis et al ( , 1987, McLain and Thangjitham (1983), and Patton-Mallory (1989) for bolted connections and by Aune and Patton-Mallory (1986a, 1986b for nailed joints.…”
Section: Fig 2 Connection Yield Strength Definitionmentioning
confidence: 76%
“…assuming that members and fas teners behave as ideal rigid-plastic materials. Numerous researchers have published verification of EYM for several connection types (Soltis et al 1986(Soltis et al , 1987McLain and Thangjitham 1983;Whale and Smith 1986). A typical example of predictive ability is seen in Fig.…”
Section: New Behavioral Equationsmentioning
confidence: 99%